Effects of methane outgassing on the Black Sea atmosphere - K. Kourtidis; I. Kioutsioukis; D. F. McGinnis; S. Rapsomanikis (Atmospheric Chemistry and Physics, 2006)
Methane in air and seawater was measured in the Eastern Black Sea during the 10–18 December 1999 BIGBLACK project cruise. The measurements allowed for the calculation of supersaturation ratios and methane fluxes across the air-sea interface. CH4 mixing ratios in air were generally in the 1.8–2.0 ppmv range, while surface (4 m depth) seawater concentrations varied from 4 to 93 ppmv. Above active seep areas, the water was supersaturated to around 500% with respect to the overlying atmosphere. Accordingly, flux densities varied greatly and were up to 3300 umol m−2 day−1. In the Sevastopol harbour, supersaturations up to around 3000%, similar to those at the Danube Delta, were observed, while in the Istanbul harbour supersaturations could not be determined because the very high values of water concentrations led to detector saturation. Simple modelling shows that the observed fluxes do not have any substantial impact on the methane content of the Black Sea atmosphere, as they would only raise its concentrations by less than 50 ppt. On the other hand, calculations performed as part of the CRIMEA project show that mud volcano eruptions could episodically raise the methane concentrations well above their regional background for several tens of kilometres downwind. These calculations, which also apply to mud volcano eruptions elsewhere on the globe, indicate that the spatial extend and the magnitude of the atmospheric perturbation is such that its observation might lie within the capabilities of existing satellite instrumentation such as SCIAMACHY on ENVISAT.